KEKUATAN PEMBUKTIAN ALAT BUKTI CCTV (CLOSED CIRCUIT TELEVISION) DALAM PERKARA TINDAK PIDANA UMUM BERDASARKAN PUTUSAN MAHKAMAH KONSTITUSI NO.20 PUU-XIV/2016 - Adzkari, Feby; Rahmat, Diding (LEX LAGUENS: Jurnal Kajian Hukum dan Keadilan, 2024)
This research examines the evidentiary strength of CCTV (Closed Circuit Television) evidence in general criminal cases based on Constitutional Court Decision No. 20/PUU-XIV/2016. The main focus of this research is how CCTV evidence is regulated in Indonesian laws and regulations and what is the evidentiary strength of CCTV evidence in general criminal cases following the Constitutional Court decision no. 20/PUU-XIV/2016. This research is normative juridical research which uses a statutory approach and a conceptual approach. The research results show that although the Criminal Procedure Code (KUHAP) does not explicitly mention CCTV as evidence, CCTV recordings can be considered as evidence of instructions or letters if they meet the authentication and reliability requirements in accordance with the Information and Electronic Transactions Law ( ITE Law). Constitutional Court Decision No. 20/PUU-XIV/2016 provides legal certainty that CCTV footage can be accepted as valid evidence in the criminal justice process if it meets these requirements. The implications of this decision strengthen the legitimacy of CCTV recordings in the criminal justice system in Indonesia, increase the effectiveness of law enforcement, and ensure the protection of individual rights.